The Influence of the Teaching Factory on the Creativity and Innovation of Vocational Learning for Student in Bandung Cicendo Special School - Aulia, Muhammad Nugraha (Angstrom Centre of Education, 2023)
This article discusses research that aims to find out how the teaching factory influences the creativity, competence, and innovation of SLB Cicendo Bandung students. The influence of the application of teaching factory on vocational learning on creative catering, developing competencies, producing new innovative products. Vocational catering is a special skill that can help students to be more independent. This learning can create an environment for students to gain experience making products, improve skills, so they can balance their abilities and knowledge. The population of this study were Cicendo Bandung SLB students who took part in the Teaching Factory program. This study uses the method of literature study and quantitative methods with data collection instruments using a questionnaire through the Google Form. This research questionnaire is a type of closed questionnaire, where the researcher gives the opportunity to respondents to give opinions on their choices. From the results of the study there were 23 respondents, 84.4% stated that the teaching factory program could affect student creativity, competence, and innovation, while 15.6% felt that it had little effect on student creativity, competence, and innovation. From the results of this study it can be concluded that teaching factory can be a program that supports student learning, especially for Cidenco SLB students. Because with this program students can be creative, innovate and practice their abilities directly in preparing themselves to enter the world of work. Therefore, it is hoped that the government and schools will be more aggressive in procuring this program.